Me Pemberian Layanan Informasi Menggunakan Media Video Animasi Untuk Meningkatkan Pemahaman Cyberbullying Siswa Kelas X Di SMK Negeri 4 Kota Bengkulu: Abstrak, Pendahuluan, Metode Penelitian, Hasil Penelitian dan Pembahasan, Kesimpulan, Daftar Pustaka - Rahma Pratiwi; I Wayan Dharmayana; Sri Saparahayuningsih (UNIVERSITAS BENGKULU, 2023)
The purpose of this study was to determine the effect of providing information services using animated video mediato increase understanding cyberbullying class X students at state vocational school 4 Bengkulu City. This researchis an experimental research with one group pre-test post-test design. The research sample is determined by thetechnique purposive sampling class X PPLG 1 totaling 26 students. Data was collected using a test instrument withtwo true-false choices. Data were analyzed using the formula t test. The results of the research show an average understanding cyberbullying before being given treatment it was in the medium category and after being giventreatment it was in the high category with t= -12.856 (p <0.05). So, information services using animated video media are effective in increasingunderstanding cyberbullying class X PPLG 1 at state vocational school 4 Bengkulu City. This study suggests guidance and counseling teachers to use information services using animated video media to increaseunderstanding cyberbullying student.